Konstruksi Makna Wahyu pada Channel Youtube MTA Internasional Berdasarkan Analisis Framing Robert N. Entman - Martadinata, Tata (Jurnal Mahardika Adiwidia, 2021)
Ahmadiyya introduces his teachings and communicates with fellow organization members through the media, one of which is the Muslim Television of Ahmadiyya (MTA). MTA tries to frame an information so that it creates the meaning desired by this organization. The purpose of this study is to know the meaning construction of revelations broadcast on the talk show program on the MTA with the Framing approach, and to know the framing of the Essence of Islamic Teaching talk show broadcast on the MTA International channel with Gamson and Mondigliani framing analysis. The result of the research is that MTA positions Wahyu as a means of connecting God and his servant. Regarding this, the door is believed to be still open and will never be closed. Because from the aspects conveyed by the media, all of them indicate that revelation will continue to exist at various levels. MTA with its program has proven that there is a construction of the meaning of revelations broadcast in the talk show of the Essence of Islamic Teachings in the form of: Define Problems, Diagnose Causes, Make Moral Judgment, Treatment Recommendations and in the form of Metaphors, Catchphrases, Depiction, Exemplar, Visual Images, Roots, Appeal to Principles, Consequences.